1979
DOI: 10.1128/jb.137.3.1088-1094.1979
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the ftsA gene product

Abstract: A nonsense mutation was identified in the essential cell division gene ftsA of Escherichia coli. A A-transducing phage was isolated which complemented this mutation. This phage programmed the synthesis of four bacterial proteins in UVirradiated cells. By substituting the nonsense mutation for the ftsA+ allele in this transducing phage and comparing the proteins programmed by it in UV-treated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…Although the dcw gene cluster of S. pneumoniae is reduced in comparison to those of other bacteria, the gene encoding FtsA maintains a conserved chromosomal position upstream of ftsZ (Massidda et al, 1998). As previously reported for E. coli and Caulobacter crescentus (Lutkenhaus and Donachie 1979;Sackett et al, 1998), we found that ftsA is not dispensable in S. pneumoniae, as suggested by the inability to recover transformants carrying the inactivated gene. Although polarity effects on the essential ftsZ gene cannot be completely ruled out in these experiments, our method has been shown to reduce this risk in previous experiments in which it allowed the detection of other nonessential S. pneumoniae genes (Fadda et al, 2003) that have been classified as essential by other methods (Thanassi et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Although the dcw gene cluster of S. pneumoniae is reduced in comparison to those of other bacteria, the gene encoding FtsA maintains a conserved chromosomal position upstream of ftsZ (Massidda et al, 1998). As previously reported for E. coli and Caulobacter crescentus (Lutkenhaus and Donachie 1979;Sackett et al, 1998), we found that ftsA is not dispensable in S. pneumoniae, as suggested by the inability to recover transformants carrying the inactivated gene. Although polarity effects on the essential ftsZ gene cannot be completely ruled out in these experiments, our method has been shown to reduce this risk in previous experiments in which it allowed the detection of other nonessential S. pneumoniae genes (Fadda et al, 2003) that have been classified as essential by other methods (Thanassi et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In E. coli and Bacillus subtilis , FtsA depends upon FtsZ for localization to the cytokinetic ring (Addinall and Lutkenhaus, 1996;Feucht et al ., 2001), and FtsA can colocalize with non-ring structures of FtsZ, such as arcs or spirals (Addinall and Lutkenhaus, 1996;Ma et al ., 1996;Ben-Yehuda and Losick, 2002). E. coli and C. crescentus cells with temperature-sensitive alleles of ftsA form long filaments with shallow constrictions when grown at the non-permissive temperature, indicating that FtsA is required for the progression of cell division (Osley and Newton, 1977;Lutkenhaus and Donachie, 1979;Ohta et al ., 1997). FtsA is also required for the recruitment of many other cell division proteins, including FtsQ (Chen et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cells retained by the membranes were resuspended in nutrient broth and grown overnight at 30"C before being plated to give individual colonies, and then replica plated at 30°C and 42°C. Apparent temperature-sensitive division mutants were screened for linkage to leu by PI-mediated transduction and then tested with a series of specialized x transducing phage (\16-2, XFH16, Xddr) in order to establish their identity (Lutkenhaus and Donachie, 1979;Begg ef al., 1980;Lutkenhaus ef al.. 1980). Mutations were further subdivided into salt-reversible and nonsalt-reversible alieles, depending on whether the presence of 1 % (w/v) NaCI in the medium would reverse the temperature-sensitive character of the mutant under test.…”
Section: Ultra-violet (Uv)'light-induced Mutagenesis and Selection Ofmentioning
confidence: 99%